2019
DOI: 10.1016/j.cemconres.2019.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the bond behaviour of corroded smooth and ribbed rebars with acoustic emission monitoring

Abstract: Assessing the bond behaviour of corroded smooth and ribbed rebars with acoustic emission monitoring. Cement and Concrete Research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…Most of the papers have used AE to identify the destruction process of materials in structures [21,22,23,24,25,26,27,28] including crack orientation [29,30,31]. The AE method is still used and improved for the purpose of the identification of failure processes [32,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the papers have used AE to identify the destruction process of materials in structures [21,22,23,24,25,26,27,28] including crack orientation [29,30,31]. The AE method is still used and improved for the purpose of the identification of failure processes [32,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…In the field of civil engineering, the AE technique has been widely used for structural health monitoring (SHM) and assessment of steel corrosion damage, especially in the evaluation of corroded concrete structures [6,7,[18][19][20][21][22]. This AE technique was operated without disturbances to the processes and progressions associated with concrete structures [23][24][25][26].…”
Section: Corrosion Assessment Using Ae Techniquementioning
confidence: 99%
“…Previous research work focused on the correlation between AE and the failure processes of each of the composite components based on the sound spectrum [ 40 , 41 , 42 , 43 , 44 , 45 ]. It has been found that, for the accurate recognition of composite failure processes, the AE recording should be expanded to include the analysis of each sound separately (as well as a single signal in a very small range of frequencies) and the analysis of the range of sounds corresponding to a given mechanical effect with the use of an acoustic spectrum.…”
Section: Introductionmentioning
confidence: 99%